Positive youth development: An experimental trial with unattached adolescents. (August 2018) - Hull, Darrell M.; Saxon, Terrill F.; Fagan, Marcus A.; Williams, Lincoln O.; Verdisco, Aimee E.
Abstract: Adolescents who are unemployed and do not attend school or other education face a variety of short- and long-term challenges ranging from economic instability to increased drug and alcohol abuse to loss of quality adjusted life years. Intervention programs that reinforce positive youth behaviors may provide more effective solutions to adolescent challenges than programs that attempt to curb maladaptive behaviors. We conducted a longitudinal randomized trial of a residential positive youth development program including a six-month job internship with youth in Jamaica ( N  = 785, 59.3% Female, Mean Age = 18.3, SD  = 1.7), which revealed significant main effects on the acquisition of workplace skills and career self-efficacy. Smaller effects were noted for youth assets in unattached Jamaican adolescents based on follow-up six months post treatment.